1983
DOI: 10.1080/02626668309491980
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater infiltration into a bare loamy sand

Abstract: In order to design micro-catchment water harvesting systems in the Indian desert, rainwater infiltration experiments were conducted on a representative loamy sand soil for a period of six years. Plots with three slopes -0.5, 5 and 10%, and five slope lengths -5.12, 7.0, 8.5, 10.75 and 14.5 m were used. With dry antecedent soil conditions, infiltration is governed by rainfall depth, whereas with wet antecedent soil conditions, raindrop impact (intensity) which forms a crust over the soil surface, is the decidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 4 publications
2
22
0
1
Order By: Relevance
“…Bryan and Poesen (1989) and Slattery and Bryan (1992) also found that rilling increased infiltration. De Ploey et al (1976), Sharma et al (1983) and Djorovic (1980) observed an increase in runoff with increasing slope angle and this was attributed to a decrease in depressional storage and ponding depth. Govers (1990) showed that slope had a significant negative effect due to differential soil cracking.…”
Section: Introductionmentioning
confidence: 95%
“…Bryan and Poesen (1989) and Slattery and Bryan (1992) also found that rilling increased infiltration. De Ploey et al (1976), Sharma et al (1983) and Djorovic (1980) observed an increase in runoff with increasing slope angle and this was attributed to a decrease in depressional storage and ponding depth. Govers (1990) showed that slope had a significant negative effect due to differential soil cracking.…”
Section: Introductionmentioning
confidence: 95%
“…As slope gradient increases, some studies observed a decrease resulting from a thinning and/or disruption of the crust (Poesen 1984), rills' formation Slattery and Bryan 1992), differential soil cracking (Govers 1990), and greater ponding depth (Fox and others 1997), a Correlation is significant at the 0.01 level (2-tailed); R c and R h are runoff coefficient and rainfall amount, and I m , I 10 and I 30 are mean rainfall intensity, maximum 10-minute rainfall intensity, and maximum 30-minute rainfall intensity, respectively etc. However, De Ploey and others (1976), Sharma andothers (1983), andDjorovic (1980) observed an increase in runoff which was attributed to a decrease in depressional storage and ponding depth. Lal (1976) and Mah and others (1992) did not find any significant effect of slope angle on runoff.…”
Section: Effect Of Slope Gradientmentioning
confidence: 99%
“…On the other hand, under conditions of low (0.6 mm·min -1 ) and high (2.12 and 2.54 mm·min -1 ) rainfall intensities, surface runoff increased with slope gradient increased (Figure 4a). One explanation for this was that infiltration rate decreased with increasing slope gradient (Sharma et al, 1983).…”
Section: Rainfall Intensity and Slope Gradient Effects On Runoffmentioning
confidence: 99%